Medicinal Plants used for Antihypercholesterolemia in Ethnic Groups of Celebes Island, Indonesia: Pemanfaatan Tumbuhan Obat sebagai Antihiperkolesterolemia di Berbagai Etnis di Pulau Sulawesi, Indonesia - Rahmawati, Nuning; Haryanti, Sari; Yanti Marfuatush Sholikhah, Ika; Subositi, Dyah; Widodo, Harto; Mujahid, Rohmat; Widiyastuti, Yuli (Universitas Tidar, 2023)
This study aimed to identify the utilization of medicinal plants used by selected traditional healers who met inclusion criteria to treat high cholesterol levels in ethnic groups of Celebes Island, Indonesia. Data collection was carried out through interviews, observation, and sample collection. This study revealed 67 concoction information and identified the use of 48 plant species distributed in 32 families among 39 healers in 20 ethnic groups in Celebes Island. Peperomia pellucida (L.) Kunth (UV=0.21), lamiaceae (15.63%), and leaves (57.35%) were determined as the most prominent species, family, and plant part used. The most widely prescribed rule of use is internal administration (94.03%) with a frequency of 3x1 per day (44.78%) for a week to a month (56.72%). However, conservation efforts need to be initiated immediately since more than 50% of healers made no cultivation efforts